PENGARUH PARTISIPASI PENYUSUNAN ANGGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KETIDAKPASTIAN LINGKUNGAN, KOMITMEN ORGANISASI DAN PELIMPAHAN WEWENANG SEBAGAI VARIABEL MODERATING ( Studi Kasus pada Politeknik Ilmu Pelayaran Semarang) - Ardiani Ika S.; Dian Triyani; Anik Puji Lestari (Universitas Muhammadiyah Semarang, 2011)
By using the contingency approach, this study is to test the moderating effect of environmentaluncertainty, organizational commitment and delegation of authority to the relationship in the participation ofthe budgeting and managerial performance. Common issues in this research is the lack of attention to theleadership of staff and lack of maximum delegation of authority to staff in participatory budgeting affectingmanagerial performance. The study population consists of affairs chief, the head unit and found the head ofdepartment at the Polytechnic of Semarang Sailing Science numbered 34 people. Technique sampling used is thecensus sample.Data collection techniques in this research is to use a questionnaire. Variables used in this researchare budgetary participation, managerial performance and environmental uncertainty, organizationalcommitment and delegation of authority as a moderating variables. The result of this research are, first,budgetary participation has significantly effecting to managerial performance. Second, environmentaluncertainty moderates the effect of budgetary participation on managerial performance. Third, organizationalcommitment moderates the effect of budgetary participation on managerial performance. Fourth, the delegationof authority moderates the effect of budgetary participation on managerial performance.